Russian roulette - Horowitz, Anthony, 1955- (London : Walker Books, 2013)
Presented with an unexpected assignment, Alex Rider's greatest nemesis, Yassen Gregoravich, recalls his life and the path that led him to become an assassin while his one-time friend, Alex's uncle, became a spy.
5.1
5-8.
5-8
Keywords: Assassins -- Juvenile fiction; Orphans -- Juvenile fiction; Adventure and adventurers -- Fiction; Assassins -- Fiction; Orphans -- Fiction; Adventure fiction; Assassins -- Fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / General; Orphans -- Fiction; Russia (Federation) -- History -- 1991- -- Juvenile fiction; Russia (Federation) -- History -- 1991- -- Fiction; Russia -- History -- 1991- -- Fiction; Adventure fiction